Esophageal Web in a Down Syndrome Infant-A Rare Case Report - Nirmala Thomas; Roy J. Mukkada; Muhammed Jasim Abdul Jalal; Nisha Narayanankutty (MDPI AG, 2018)
We describe the rare case of an infant with trisomy 21 who presented with recurrent vomiting and aspiration pneumonia and a failure to thrive. Infants with Down's syndrome have been known to have various problems in the gastrointestinal tract. In the esophagus, what have been described are dysmotility, gastroesophageal reflux and strictures. This infant on evaluation was found to have an esophageal web and simple endoscopic dilatation relieved the infant of her symptoms. No similar case has been reported in literature.